Tubulin Post-translational Modifications: Potential Therapeutic Approaches to Heart Failure - Liu, Chang; Chen, Yuwen; Xie, Yao; Xiang, Meixiang (Frontiers in Cell and Developmental Biology, 2022)
In recent decades, advancing insights into the mechanisms of cardiac dysfunction have focused on the involvement of microtubule network. A variety of tubulin post-translational modifications have been discovered to fine-tune the microtubules’ properties and functions. Given the limits of therapies based on conserved structures of the skeleton, targeting tubulin modifications appears to be a potentially promising therapeutic strategy. Here we review the current understanding of tubulin post-translational modifications in regulating microtubule functions in the cardiac system. We also discussed how altered modifications may lead to a range of cardiac dysfunctions, many of which are linked to heart failure.